MUET webinar 2025: question format overview - Joseph, Stefanie Natasha Rich; Robert, Cindy; Jeri, Shirley Clare (Corporate Communication Unit, UiTM Mukah Campus, 2025)
The webinar served as an informative platform to prepare candidates for the upcoming MUET in November 2025. It highlighted crucial aspects of the MUET format, providing students with valuable guidance on test requirements and strategies. Distinguished speakers included Ms. Cindy Robert of UiTM Mukah, Madam Sara Ruran Fabian of Politeknik Mukah, and Mr. Daryl Albright of Kolej Vokasional Betong, each sharing their expertise and insights on different components of the examination.